Composição química e atividade antitumoral da geoprópolis de Melipona fasciculata Smith - CUNHA, Mayara Soares (2017)
Melipona fasciculata Smith (tiúba) is widely cultivated in the state of Maranhão, mainly in the Baixada and Cerrado regions, and is a stingless bee that produces honey, wax and geopropolis, which consists of resinous material collected from vegetable species, mixed with wax, salivary secretions and soil. Studies have shown that the thropic geopropolis has several biological activities, such as antimicrobial, leishmanicide, anti-helminthic, anthelmintic and antiproliferative, proving to be a promising natural product for further research. Therefore, the objective of this work was to evaluate the chemical composition by LC-MS-MS And the antitumor potential of extracts of geopropolis of Melipona fasciculata of Baixada and Cerrado of Maranhão. The geopropolis samples were collected in the municipality of Fernando Falcão, Cerrado and Palmeirândia-MA, Baixada, and the collection of the Cerrado geopropolis was punctual and the collection of the Baixada geopropolis was temporary, but all samples were submitted to extractive process with 70% hydroethanol solution, by steeping for 48h. Because of the different geopropolis samples, it was possible to develop two studies, the first one was the Cerrado sample whose EGP extract was submitted to fractionation with increasing polarity solvents and the evaluation of the chemical composition, phenolic content, activity antioxidant and cytotoxic action for Ehrlich tumor cells, MCF-7 and RAW. The results of this first work showed that EGP and its fractions ethyl acetate (FA) and hydrometanic fraction (FM) have high levels of phenolic compounds and antioxidant activity and that both EGP and these two fractions (FM and FA) present the best cytotoxicity for tumor cells. In the EGP extract it was possible to identify 10 substances all as hydrolysable tannins derived from gallic acid and ellagic acid. In the second work, with samples from the Baixada geopropolis, the collection was randomized and annual, obtaining six samples and consequently six extracts, encoded from EG1 to EG6 and evaluating the cytotoxicity to Erhlich tumor cells and consequently screening for evaluation of the chemical composition and antitumor action in vivo with Ehrlich tumor in ascitic and solid form. The results showed that the extracts of the geopropolis had an inhibitory concentration (IC50) of 180 to 419 μg / mL for cytotoxicity with tumor cells, being selected four more cytotoxic extracts and with more similar chemical profile to identify their constituents, that by comparison with data In the literature it was possible to tentatively identify 13 substances, among them, triterpenes, benzophenones and an alkaloid. Thereafter, a more cytotoxic in vitro and higher yielding extract was selected for in vivo antitumor evaluation and the results demonstrated that EG1 inhibited the development of Ehrlich ascites tumor, as it reduced the number of tumor cells, ascites volume, and increased survival of the mice and that when administered prophylactically and therapeutically on Ehrlich solid tumor, doses of 0.5 and 5 mg/kg inhibited tumor development when compared to control and dose 50 mg/kg. Based on the results, it was observed that the geopropolis of M. fasciculata from Baixada and Cerrado do Maranhão possess an antitumor potential, but with different chemical composition, consequently they act by different therapeutic mechanisms, being necessary the continuation of these studies for the complete discovery of these mechanisms of Responsible for cytotoxic activity